REVIEW: PEMANFAATAN BROMELAIN PADA BEBERAPA PANGAN LOKAL INDONESIA - Warsono El Kiyat; Kevin Reynaldo; Jeremiah Irwan (Jurnal Agroteknologi, 2019)
Bromelain is one of the protease that can be produced from all of parts of the pineapple plants (Ananas comosus). It has potential to improve quality of local Indonesian food such as tempeh gembus, virgin coconut oil (VCO), and dumbo catfish based fish sauce (DCBFS). Tempeh gembus is a traditional food that has unique characteristics especially in its taste because it contains amino acids. VCO attracts consumers because of its health aspect. Its raw materials are available in Indonesia. DCBS  is a product of fermented fish with salt that has a distinctive taste and is produced in Indonesia. This study aimed to analyze the effect of bromelain on local Indonesian food and its applications. The result showed that the use of bromelain in local Indonesian food could improve the quality and nutritional value of local food. Bromelain can be used in local food like tempeh gembus, virgin coconut oil, and fish sauce from dumbo catfish. The use of bromelain in tempeh gembus could  increase both of the water-soluble nitrogen level and the pH value. However, the addition of bromelain in the production of virgin coconut oil and fish sauce from dumbo catfish could increase the yield of theirs. .